A small noncoding RNA signature found in exosomes of GBM patient serum as a diagnostic tool. Issue 4 (16th January 2014) - Manterola, Lorea; Guruceaga, Elizabeth; Pérez-Larraya, Jaime Gállego; González-Huarriz, Marisol; Jauregui, Patricia; Tejada, Sonia; Diez-Valle, Ricardo; Segura, Victor; Samprón, Nicolás; Barrena, Cristina; Ruiz, Irune; Agirre, Amaia; et al.
Abstract: Background: Glioblastoma multiforme (GBM) is the most frequent malignant brain tumor in adults, and its prognosis remains dismal despite intensive research and therapeutic advances. Diagnostic biomarkers would be clinically meaningful to allow for early detection of the tumor and for those cases in which surgery is contraindicated or biopsy results are inconclusive. Recent findings show that GBM cells release microvesicles that contain a select subset of cellular proteins and RNA. The aim of this hypothesis-generating study was to assess the diagnostic potential of miRNAs found in microvesicles isolated from the serum of GBM patients. Methods: To control disease heterogeneity, we used patients with newly diagnosed GBM. In the discovery stage, PCR-based TaqMan Low Density Arrays followed by individual quantitative reverse transcriptase polymerase chain reaction were used to test the differences in the miRNA expression levels of serum microvesicles among 25 GBM patients and healthy controls paired by age and sex. The detected noncoding RNAs were then validated in another 50 GBM patients. Results: We found that the expression levels of 1 small noncoding RNA (RNU6-1) and 2 microRNAs (miR-320 and miR-574-3p) were significantly associated with a GBM diagnosis. In addition, RNU6-1 was consistently an independent predictor of a GBM diagnosis. Conclusions: Altogether our results uncovered a small noncoding RNA signature in microvesicles isolated from GBM patient serum that could be used as a fast and reliable differential diagnostic biomarker.